Generalization of zad strategy: an application to a dc-dc buck converter (2011)
The Zero Average Dynamics (ZAD) strategy has been reported in the last decade as an alternative for controlling power converters. This technique has the advantage of guaranteeing fi xed frequency switching. However, the stability of the controller is highly dependent on the load value, and when the stability is lost, the fi xed frequency switching is lost too. In this paper we generalize ZAD strategy using the probabilities framework through the expectation operator. Thus, we recover classical sliding mode control classical ZAD strategy, and new control methods can be defined, which are more stable than the others previously used. For this reason, this technique is entitled Generalized Zero Average Dynamics (GZAD). We will show several simulations regarding an application to a DC-DC Buck converter within the generalized ZAD strategy, which cannot be deduced from the classical ZAD. Numerical simulations show good regulation features and a wide range of stability.